Production Scheduling Approach Using the Theory of Constraint (TOC) Method at PT. King of Indonesia Perkasa Suwayuwo Pasuruan - Saikhu Rakhman , Muhammad; Pusakaningawati, Ayik (Journal Knowledge Industrial Engineering (JKIE), 2024)
This research aims to overcome the problem of production delays at PT. The King of Indonesia Perkasa Suwayuwo Pasuruan by applying the Theory of Constraints (TOC). Production data shows that available capacity (870 units/month) is insufficient demand (1,000 units/month), with bottlenecks at workstations in week 4. Data collection methods include observation, interviews, and documentation studies. The solution tested was the addition of overtime (5 hours/day) and additional shifts (16 hours/day). The results showed that additional shifts were more effective, increasing capacity to 1,752 units/month and reducing delays by 20%. This research makes a practical contribution to production optimization through the identification of constraints and resource reallocation.